Willingness to provide behavioral health recommendations: a cross-sectional study of entering medical students - McCurdy, Stephen A (BioMed Central, 2012)
BACKGROUND: Behavioral factors contribute importantly to morbidity and mortality, and physicians are trusted sources for information on reducing associated risks. Unfortunately, many clinical encounters do not include prevention counseling, and medical school curriculum plays an important role in training and promoting such counseling among medical students. METHODS: We surveyed all 93 freshman medical students at entry to the University of California, Davis School of Medicine in 2009 to evaluate baseline knowledge of population health principles and examine their approach to clinical situations involving four common behavioral risk factors illustrated in brief clinical vignettes: smoking, alcohol use in a patient with indications of alcoholism, diet and exercise in an overweight sedentary patient, and a 16-year-old contemplating initiation of sexual intercourse. Based on vignette responses, we assessed willingness to (1) provide information on risks, (2) recommend elimination of the behavior as the most efficacious means for reducing risk, (3) include strategies apart from elimination of the behavior for lowering risk (i.e., harm reduction), and (4) assure of their intention to continue care whether or not recommendations are accepted. RESULTS: Students answered correctly 71.4 % (median; interquartile range 66.7 % - 85.7 %) of clinical prevention and population health knowledge questions; men scored higher than women (median 83.3 % vs. 66.7 %, p<0.02). Students showed high willingness to provide information and strategies for harm reduction apart from risk elimination, while respecting patient autonomy. Willingness to recommend elimination of high-risk behaviors “always or nearly always” was high for smoking (78.5 %), alcohol consumption in a patient with indications of alcoholism (64.5 %), and diet and exercise in a sedentary and overweight individual (87.1 %), and low for the 16-year-old considering initiating sexual intercourse (28.0 %; Friedman test, p<0.001). Willingness was not associated with the respondent’s background knowledge of population health principles or gender. CONCLUSION: Students showed high willingness to educate and respect patient autonomy. There was high willingness to recommend elimination of risk behaviors for smoking, alcohol, and poor diet/exercise, but not for sexual intercourse in an adolescent considering sexual debut. Further research should address promoting appropriate science-based preventive health messages, and curriculum should include explicit discussion of content of recommendations.